2017
DOI: 10.18203/2349-2902.isj20173414
|View full text |Cite
|
Sign up to set email alerts
|

Incisional hernia: preliminary observations at a new institute

Abstract: Background: Ventral hernia develops when an area of the abdominal wall weakens and develops a tear or hole. It may develop as a defect at birth, resulting from incomplete closure of a part of the abdominal wall, or develop where an incision was made during an abdominal surgery, occurring when the incision doesn't heal properly. Incisional hernia is typically observed within the first 5 years after the surgical incision is made, but may develop long afterwards.1 This study was undertaken to review the history a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…12 Average defect size and average defect area are 7.3x6.5 cm and 47.45 cm 2 respectively. In studies by Subramanian A et al 13 and Huda F et al 14 the average area of the defect observed where 37.9±4.9 cm 2 and 35.63 cm 2 respectively similar to but less than that obtained in our study.…”
Section: Discussionsupporting
confidence: 83%
“…12 Average defect size and average defect area are 7.3x6.5 cm and 47.45 cm 2 respectively. In studies by Subramanian A et al 13 and Huda F et al 14 the average area of the defect observed where 37.9±4.9 cm 2 and 35.63 cm 2 respectively similar to but less than that obtained in our study.…”
Section: Discussionsupporting
confidence: 83%
“…In Tulaskar et al [9] study 71.8% occurred in lower midline incision and 78% incidence were due to gynecological procedures. Cesarean section was commonest preceeding surgery for incisional hernia resulted in Farhanul Hude et al study [12] . In lower abdomen, intraabdominal hydrostatic pressure (20 cm of water) is higher than upper abdomen (8cm of water) in erect posture and absence of posterior rectus sheath were the reason for frequent site of incisional hernia.In our study 38 cases (76%) showed no complication during previous surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar hernia is characterized by being reducible and more prominent with increased intra-abdominal pressure such as changing the position to sitting or standing. A contrast-enhanced computed tomography (CT) scan is the gold standard and essential examination for confirming the diagnosis of lumbar hernia as it shows protrusion and hernia sac through the musculature [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to establish the diagnosis and formulate proper management, a high suspicion index is needed. This is essential to avoid the significant risk of complications, since 25% will become incarcerated and 8% strangulated [14].…”
Section: Introductionmentioning
confidence: 99%